TRACER STUDY ALUMNI: UPAYA PENGEMBANGAN PRODI PERBANKAN SYARIAH UNIVERSITAS MUHAMMADIYAH PROF DR HAMKA - Amri, Andi; Sami Gultom, Mitra (Yayasan Indonesia Bermutu, 2024)
Tracer study is carried out in order to evaluate the study program so that it runs well according to the provisions that have been set. These provisions are made in order to create graduates from a superior study program and have a good impact on the development of the institution. This certainly applies to the Prof DR HAMKA Muhammadiyah University Sharia Banking study program which wants this study program to develop and have good quality, so tracer study is the best step in achieving this. In conducting this tracer study, there are four stages that need to be carried out, namely starting from the development of concepts and instruments, followed by data collection, then analyzing the data that has been collected, and finally preparing the tracer study report. This activity was carried out from August to early October 2023. The tracer study was conducted to alumni of the Islamic Banking Department of the Faculty of Islamic Studies, Muhammadiyah Prof DR HAMKA University who graduated in 2022. The tracer study conducted at the Islamic Banking study program at Muhammadiyah Prof DR HAMKA University used a survey method to alumni who had graduated and to graduate users. Deepening the survey results was carried out with in-depth interviews with selected alumni and graduate users to strengthen the findings of the tracer study results for the improvement of learning services in the Islamic Banking study program at Universitas Muhammadiyah Prof DR HAMKA. The results showed that the learning process provided by Prof DR HAMKA Muhammadiyah University, especially the Islamic Banking study program, has been carried out well, but there are several things that must be considered, namely increasing the understanding of Islamic Banking students in applying Al Islam Kemuhammadiyahaan and also limitations in communicating to establish cooperation so that they can get the best job.